Life-cycle cost analysis for an incremental seismic rehabilitation project - Loa G. (2021)
The author(s) disclosed receipt of the following financial support for the research, authorship, and/or publication of this article: This project was partially funded by CONCYTEC within the framework of the 027-2015-FONDECYT Agreement.